DOCUMENTS OF THE CENTRAL STATE ARCHIVE OF THE REPUBLIC OF DAGESTAN ON THE DEVELOPMENT OF THEATRE IN 1946-1960s - Kulaeva, Al'bina Dzalilovna (History, Archeology and Ethnography of the Caucasus, 2019)
The paper considers material, stored in the main reserves of the document repository of the Republic of Dagestan, as well as in the repositories directly related to the history of theatre in Dagestan in 1946-1960 period. An attempt was made within the general characteristics of the documents on the research topic to evaluate new sources which could form the basis for the development of new aspects of the problem. Special attention is paid to the general issues of the development of theatrical art of Dagestan during the period under study, reflected in the documents, as well as issues related to the functioning of Russian and national theaters, their material and technical security, the conditions of creative work and life of theater workers. During the research, documents of both the main repositories of the Central State Archive of the Republic of Dagestan, containing a generalization of the history of multinational theater in the period under study, and individual collections, funds, belonging to the Dagestan State Russian Drama Theater named after A.M. Gorkyi, national theaters of Dagestan (Kumyk Musical Drama Theater named after A.-P. Salavatov, Avar Musical Drama Theater named after G. Tsadasa, Lak Drama Theater named after E. Kapiev, Lezgin Music and Drama Theater named after S. Stalsky and etc.) have been examined. The study of archival sources makes it possible to trace patterns in the development of theatrical professional art in Dagestan as a whole, as well as to identify the distinctive features in the history of each theater and its performers. The analysis of statistical information from estimates, reports, and references leads to interesting conclusions about the priorities of the policy of the central and republican authorities and administrations in the field of theater. Biographical notes, documents on the various performances, repertoire performances, tours, staffing data provide unique material about the daily lives of theater workers.